Neospora caninum surface antigen 1 is a major determinant of the pathogenesis of neosporosis in nonpregnant and pregnant mice - Abdelbaky, Hanan H.; Rahman, Md. Masudur; Shimoda, Naomi; Chen, Yu; Hasan, Tanjila; Ushio, Nanako; Nishikawa, Yoshifumi (Frontiers in Microbiology, 2024)
NcSAG1 is one of most widely investigated antigens of Neospora caninum in various research fields. Such studies demonstrated the proficiency of NcSAG1 in the regulatory process of parasite adhesion and invasion of host cells. Accordingly, the contribution of NcSAG1 to the pathogenesis of neosporosis can undoubtedly be extrapolated, but direct evidence is lacking. Herein, we provide the first successful attempt at the gene disruption of NcSAG1 and novel data on the invasion and virulence potentials of N. caninum in vitro and in vivo. The disruption of the NcSAG1 gene was applied using the CRISPR/Cas9 system and confirmed by PCR, western blot and indirect fluorescent antibody tests as NcSAG1 knockout parasites (NcSAG1KO). Then, we investigated the role of NcSAG1 in the growth kinetics of the parasite in vitro. The deletion of the NcSAG1 gene significantly decreased the infection rate and reduced the egress rate of the parasite. An in vivo study using nonpregnant female and male BALB/c mice revealed a significantly higher survival rate and lower body weight change in the group infected with the NcSAG1KO parasite than in the parental strain (Nc-1)-infected group. Regarding the vertical transmission model of BALB/c mice, the absence of the NcSAG1 gene significantly enhanced the survival of pups and greatly lowered the parasite burden in the brains of pups. In conclusion, our study suggested NcSAG1 as a key molecule in the pathogenesis of N. caninum.